Progress towards Sustainable Utilisation and Management of Food Wastes in the Global Economy - Purabi R. Ghosh; Derek Fawcett; Shashi B. Sharma; Gerrard Eddy Jai Poinern (International Journal of Food Science)
In recent years, the problem of food waste has attracted considerable interest from food producers, processors, retailers, and consumers alike. Food waste is considered not only a sustainability problem related to food security, but also an economic problem since it directly impacts the profitability of the whole food supply chain. In developed countries, consumers are one of the main contributors to food waste and ultimately pay for all wastes produced throughout the food supply chain. To secure food and reduce food waste, it is essential to have a comprehensive understanding of the various sources of food wastes throughout the food supply chain. The present review examines various reports currently in the literature and quantifies waste levels and examines the trends in wastage for various food sectors such as fruit and vegetable, fisheries, meat and poultry, grain, milk, and dairy. Factors contributing to food waste, effective cost/benefit food waste utilisation methods, sustainability and environment considerations, and public acceptance are identified as hurdles in preventing large-scale food waste processing. Thus, we highlight the need for further research to identify and report food waste so that government regulators and food supply chain stakeholders can actively develop effective waste utilisation practices.